Sustainability Level Analysis of the Application of 21st Century Skills By University Students - Indra Primahardani; Sri Erlinda; Supentri Supentri (STAI Hubbulwathan Duri, 2024)
In order to meet the challenge of 21st-century skills, every human resource must be prepared with complex problem-solving skills. Colleges, particularly state colleges in Pekanbaru City, have a vested interest in helping their students develop 21st-century skills. To overcome these problems, we need a 21st-century approach for college students, particularly Riau University students. No one has yet evaluated the long-term viability of the use of 21st-century talents at Riau University. As a result, the author is interested in doing research to develop a strategy to improve students' 21st-century abilities at the University of Riau. The study was conducted solely on Riau University students. The Simple Random Sampling Technique was used to choose the samples. Riau University has a total of 35.785 students spread across the faculty. Based on the necessary sample size chart, the number of samples necessary is 654, with a confidence rating of 99% and a margin of error of 5%. As the results of the analysis, it is possible to identify multidimensional sustainability status at a value of 74.88, where this value is in the range of 50,01–75,00, with a fairly sustainable category. This condition gives the idea that the updating of 21st-century skills by students at Riau University is only in a sufficient category, or, in a state of warning to stakeholders. Riau University can ensure that its students not only have strong academic knowledge but also have the relevant and necessary skills to cope with the complex dynamics of the 21st century by implementing robust strategies and involving all stakeholders.